Phytochemical and Biological Characterization of the Fractions of the Aqueous and Ethanolic Extracts of Parthenium hysterophorus - Miguel A. Alfaro Jiménez; Alejandro Zugasti Cruz; Sonia Y. Silva Belmares; Juan A. Ascacio Valdés; Crystel A. Sierra Rivera (Separations, 2022)
In this study, the fractions of the aqueous (AE) and ethanolic (EE) crude extracts of Parthenium hysterophorus were evaluated for their phytochemical composition, cytotoxic, and antioxidant activity. The two extracts were subjected to a fractionation by vacuum liquid chromatography, obtaining seven fractions for each extract. These fractions were evaluated for the presence of phenolic compounds by reverse phase high performance liquid chromatography coupled to mass spectrometer (RP-HPLC-MS) analysis. Their cytotoxic activity was tested with a hemolysis assay. The antioxidant activity was evaluated with the Trolox equivalent antioxidant capacity (TEAC), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and hydroxyl radical (–OH) scavenging assays. In addition, the effect of the fractions on the activity of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), from human erythrocytes, was evaluated. The phytochemical screening by RP-HPLC-MS mainly showed the presence of flavonoids and hydroxycinnamic acids. The hemolysis assay exhibited a low cytotoxic activity by the fractions of the AE, but the fractions of the EE exhibited a hemolytic effect. The fractions of the AE and EE showed significant antioxidant activity to inhibit radicals in the three radical scavenging assays. Moreover, only some fractions of the AE showed a significant increase in the activity of the SOD enzyme, while the activity of CAT exhibited a significant increase by the fractions of the two extracts. The fractions of the AE and EE of P. hysterophorus have phytochemicals with antioxidant activity to inhibit radicals and increase the activity of in vitro antioxidant enzymes.